Occupational physical activity measurement among nurses in Universiti Malaya Medical Centre / Dr. Syamsul Rizal Bin Abu Amin - Syamsul Rizal, Abu Amin (2012)

(untitled)
Background: Although many studies have investigated the correlate of physical activity, these were mostly conducted in the leisure time domain. There is still lack of understanding about correlates physical activity exclusively in the workplace setting, as most study in the occupational domain are coupled with transportation domain. This study objectively examined the correlates of physical activity only in the occupational setting, where different backgrounds of female nurses were examined within the similar physical, social and working environment.